Method for preparing catalyst from ultrasonic-assisted modified carbon-based material and application of catalyst in catalytic methane cracking hydrogen production

The preparation of catalysts by ultrasonic assisted modification of carbon-based materials has been solved, and the problems of high cost and inactivation of catalyst materials in the prior art have been improved, the methane conversion rate and reaction efficiency have been improved, and the industrialization prospects of methane cracking are realized.

CN119386846APending Publication Date: 2025-02-07CHINA UNIV OF MINING & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411492078.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing methane catalytic cracking hydrogen production technology, the high cost of catalyst materials, easy sintering and carbon deposition lead to catalyst deactivation, and the reaction temperature is high and energy consumption is large, which affects industrial applications.

Method used

The catalyst is prepared by ultrasonic-assisted modified carbon-based materials, and 20-50 mesh coconut shell activated carbon is modified by Na2CO3 to form a catalyst with a uniform pore structure and a high specific surface area, which is used to catalyze methane cracking to produce hydrogen.

Benefits of technology

The methane conversion rate is improved, the reaction temperature is reduced, the catalyst deactivation is delayed, the production process is simplified, the subsequent separation and purification steps are eliminated, and the cost reduction and efficiency of methane cracking is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386846A_ABST
    Figure CN119386846A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a catalyst from an ultrasonic-assisted modified carbon-based material and application of the catalyst to hydrogen production through catalytic methane cracking. According to the method, the carbon-based material which is low in price, easy to obtain and high in thermal stability is used as a raw material, the catalyst with excellent methane catalytic activity is prepared by activating the carbon-based material with Na2CO3 under the assistance of ultrasonic waves, and an experiment of efficient hydrogen production through methane catalytic cracking is carried out on a fixed bed reactor; the methane cracking reaction temperature is reduced, only H2 and solid carbon are generated in reaction products, greenhouse gas is not generated, the production process is simple, and industrialization is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of methane cracking, and in particular to a method for preparing a catalyst by ultrasonically assisted modified carbon-based materials and an application of the method in catalyzing methane cracking to produce hydrogen. Background Art

[0002] As climate change and energy security issues become increasingly prominent, countries around the world are seeking to promote energy transformation and achieve green development by vigorously developing clean energy. Against the backdrop of global energy structural transformation, hydrogen energy, as a clean, efficient and renewable energy form, has received widespread attention. In nature, there is only very rare free hydrogen, and most hydrogen atoms exist in a combined state. At present, the main technologies for producing hydrogen from natural gas are: methane steam reforming, methane dry reforming, methane partial oxidation and methane cracking technology. Among them, the output of hydrogen produced by methane steam reforming accounts for 48% of the total hydrogen production. However, the products of methane steam reforming technology, except H 2 In addition, a large amount of CO 2 The subsequent separation and purification work is complicated, the purity of hydrogen cannot be guaranteed, and the process is complicated and the cost of components is high, which is not conducive to industrialization.

[0003] Methane cracking produces hydrogen by breaking the carbon-hydrogen bonds in methane molecules to generate H 2 A method for removing methane from solid carbon. The only gas product of this technology is hydrogen. No additional separation technology is required, which simplifies the production process and reduces the cost of hydrogen production. However, due to the extremely strong stability of methane molecules, a high conversion rate can usually be achieved above 1200°C, which places higher requirements on energy consumption and reactor materials. In order to reduce the activation energy of the methane cracking reaction and thereby increase the methane conversion rate, a methane catalytic cracking hydrogen production technology was proposed. In the hydrogen production process, the selection of catalyst materials with high catalytic activity and high stability is the key to this technology. Metal catalysts such as Ni, Co, and Fe are widely used in methane catalytic cracking hydrogen production technology due to their good catalytic activity, but the high cost of metal catalyst materials, easy sintering, and catalyst deactivation caused by carbon deposition limit their industrial applications. The specific technical disadvantages are as follows:

[0004] (1) At present, the main method of producing hydrogen from methane is methane steam reforming technology. The main reaction of this technology is: CH 4 +H 2 O→CO 2 +3H 2 ΔH 298K =206 kJ / mol, because the reaction needs to absorb a lot of heat and the product contains greenhouse gas component CO 2 , further separation and purification are required, which increases the cost of hydrogen production.

[0005] (2) The carbon-hydrogen bonds in the methane molecule have good symmetry and stability, making methane a very stable molecule. Therefore, the reaction temperature of methane thermal cracking hydrogen production technology is usually higher than 1200°C. The reaction consumes a lot of energy and places higher requirements on the reactor material.

[0006] (3) The catalysts currently used for catalytic cracking of methane are mainly metal catalyst materials such as Ni, Co, and Fe. Although these catalyst materials show high catalytic activity in the catalytic methane cracking reaction, their industrial application is affected by the rapid deactivation of the catalyst materials due to problems such as sintering and carbon deposition, as well as their high cost.

[0007] (4) Carbon-based catalyst materials are used for catalytic cracking of methane to produce hydrogen due to their wide availability, low price, high thermal stability and sulfur resistance, but their catalytic methane cracking efficiency is low.

[0008] In order to reduce costs and increase efficiency, the application of carbon-based materials in catalytic methane cracking technology has been studied. Carbon-based materials are low-priced, widely available, and have high thermal stability and sulfur resistance. They are good catalysts for catalytic methane cracking to produce hydrogen. However, compared with metal catalyst materials, the efficiency of catalytic methane conversion by carbon-based materials is still somewhat insufficient.

[0009] Modifying carbon-based materials to enrich the functional groups on the catalyst surface and increase the active sites can improve the catalytic activity of methane cracking reactions. However, in the process of preparing catalyst materials using conventional modification techniques, it is impossible to penetrate deep into the internal pore structure of the catalyst, resulting in uneven distribution of catalyst pore size, which in turn affects the catalytic activity of the prepared catalyst.

[0010] CN113307225A discloses a method and application of using carbon black to enhance activated carbon to stably catalyze methane cracking and hydrogen production. 8-16 mesh coconut shell activated carbon is used as a carrier to load carbon black, and two carbon catalysts are combined through a series of preparation processes, and reacted at 850-1000℃ under normal pressure. The catalyst has a higher initial conversion rate and shows a delayed deactivation effect. However, this technical solution loads carbon black on the surface of the activated carbon catalyst, and requires a series of steps such as acid washing. The entire catalyst preparation process is complicated and has a long cycle.

[0011] CN106865498B discloses a method for preparing hydrogen and fiber carbon using carbon materials as catalysts, using a mixed gas containing methane and hydrogen as a raw material, using carbon materials as catalysts, and reacting at 600-1200°C and normal pressure. Among them, hydrogen accounts for 1% to 90% of the total flow of the mixed gas. This method effectively improves the stability of carbon materials catalyzing methane cracking to produce hydrogen. However, this technical solution changes the raw gas components and introduces a mixture of methane and hydrogen, but does not fundamentally improve the methane conversion rate. Summary of the invention

[0012] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a catalyst from a carbon-based material assisted by ultrasound and its application in catalytic methane cracking to produce hydrogen. The catalyst of the present invention uses 20-50 mesh coconut shell activated carbon as raw material, and uses Na 2 CO 3 Carbon-based catalysts prepared from modified activated carbon can be used to catalyze methane cracking to produce hydrogen, and have broad industrial prospects.

[0013] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0014] A method for preparing a catalyst by ultrasonically assisted modification of a carbon-based material comprises the following steps:

[0015] Step 1, preprocessing

[0016] Take 20-50 mesh coconut shell activated carbon, wash it repeatedly with deionized water to remove dust and impurities on the surface of the activated carbon until the washing water is clear, dry it and set it aside;

[0017] Step 2, ultrasonic treatment

[0018] Take anhydrous sodium carbonate to prepare a 0.05-0.6 mol / L sodium carbonate solution, completely immerse the coconut shell activated carbon cleaned in step 1 in the sodium carbonate solution, and then place it in an ultrasonic cleaning machine for ultrasonic oscillation for 2 hours to obtain coconut shell activated carbon;

[0019] Step 3, static modification

[0020] Take out the coconut shell activated carbon after ultrasonic oscillation treatment, let it stand at room temperature, stir the activated carbon thoroughly every 30 minutes to allow the bubbles on its surface to escape, and finally dry it for use;

[0021] Step 4, Calcination

[0022] The coconut shell activated carbon modified in step 3 is placed in a tubular furnace, calcined under nitrogen protection, and kept warm for 3 hours to remove volatile matter and bound water in the activated carbon, thereby obtaining a catalyst.

[0023] As an improvement, the drying temperature in step 1 and step 3 is both 105° C., and the drying time is both 6 hours.

[0024] As an improvement, the nitrogen introduction rate in step 4 is 40 ml / min.

[0025] As an improvement, the calcination temperature in step 4 is 1000°C and the heating rate is 10°C / min.

[0026] The catalyst prepared by the above method has an irregular honeycomb porous structure, the pores are evenly distributed and have a large depth, and the surface roughness is significantly improved.

[0027] The catalyst prepared by the above method is used in catalytic methane cracking to produce hydrogen.

[0028] As an improvement, the cracking temperature is 900° C. and the methane gas flow rate is 5 ml / min.

[0029] Beneficial effects:

[0030] Compared with the prior art, the present invention provides a method for preparing a catalyst by ultrasonically assisted modification of carbon-based materials and its application in catalytic methane cracking to produce hydrogen. The method uses cheap, readily available and highly thermally stable carbon-based materials as raw materials, and utilizes ultrasonically assisted Na 2 CO 3 The activated carbon-based material reaches the internal pores of the catalyst material, making the pore structure of the catalyst material more uniform, which is conducive to the adsorption of methane molecules at the active sites. The high-efficiency hydrogen production experiment of methane catalytic cracking was carried out in a fixed-bed reactor. The obtained catalyst not only improved the methane conversion rate, but also reduced the methane cracking reaction temperature. In addition, the reaction product was only H 2 It does not produce solid carbon, does not generate greenhouse gases, has a simple production process, and does not require further separation and purification. It can achieve cost reduction and efficiency improvement in the methane cracking process for hydrogen production and is easy to industrialize.

[0031] The specific advantages are as follows:

[0032] (1) The raw materials of the catalyst of the present invention are cheap and readily available, the cost is low, the preparation cycle is short, and it is suitable for industrial promotion and application;

[0033] (2) The present invention uses ultrasound-assisted modified carbon-based materials to prepare the catalyst. The ultrasound-assisted modified carbon-based materials can reach the internal pores of the catalyst, making the pore structure of the catalyst more uniform, which is conducive to the adsorption of methane molecules at the active sites and improving the catalytic efficiency;

[0034] (3) The present invention uses activated carbon materials with a wide range of sources, large specific surface area and good sulfur resistance to prepare Na 2 CO 3 Modified activated carbon catalysts are used in methane catalytic cracking to produce hydrogen. This not only reduces the reaction temperature and improves the methane conversion rate, but also produces only hydrogen as the gaseous product, eliminating the need for subsequent separation and purification processes and simplifying the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a process flow chart of a method for preparing a catalyst by ultrasonically assisted modification of carbon-based materials according to the present invention;

[0036] Figure 2 The methane conversion rates of the ultrasonically assisted modified activated carbon and the unmodified activated carbon of the present invention at different temperatures, wherein (a) is 850°C, (b) is 900°C, and (c) is 950°C;

[0037] Figure 3 Surface morphologies of different catalysts, where (a) is an activated carbon catalyst at ×500 times, (b) is an activated carbon catalyst at ×1000 times, (c) is a catalyst of a carbon-based material modified by ultrasound-assisted 0.2 mol / L sodium carbonate at ×500 times, and (d) is a catalyst of a carbon-based material modified by ultrasound-assisted 0.2 mol / L sodium carbonate at ×1000 times;

[0038] Figure 4 is the methane conversion rate of different catalysts, where (a) is the adsorption-desorption isotherm, and (b) is the pore size distribution curve of the catalyst;

[0039] Figure 5 is the methane conversion rate of the catalyst at different flow rates (950℃);

[0040] Figure 6 The corresponding methane conversion rate (950℃) of the catalysts prepared by modification with different concentrations of sodium carbonate;

[0041] Figure 7 Figure 3 is the surface morphology of catalysts modified with different concentrations of sodium carbonate, where (a) is a catalyst of carbon-based materials modified with 0.05 mol / L sodium carbonate under ×500 times of ultrasonic assistance, (b) is a catalyst of carbon-based materials modified with 0.05 mol / L sodium carbonate under ×1000 times of ultrasonic assistance, (c) is a catalyst of carbon-based materials modified with 0.10 mol / L sodium carbonate under ×500 times of ultrasonic assistance, (d) is a catalyst of carbon-based materials modified with 0.10 mol / L sodium carbonate under ×1000 times of ultrasonic assistance, (e) is a catalyst of carbon-based materials modified with 0.40 mol / L sodium carbonate under ×500 times of ultrasonic assistance, (f) is a catalyst of carbon-based materials modified with 0.40 mol / L sodium carbonate under ×1000 times of ultrasonic assistance, (g) is a catalyst of carbon-based materials modified with 0.60 mol / L sodium carbonate under ×500 times of ultrasonic assistance, and (h) is a catalyst of carbon-based materials modified with 0.60 mol / L sodium carbonate under ×500 times of ultrasonic assistance. DETAILED DESCRIPTION

[0042] Example 1

[0043] Use Figure 1 The preparation process is operated, using 20-50 mesh coconut shell activated carbon as raw material, through Na 2 CO 3 The modified carbon-based material was used to prepare a catalyst for catalytic cracking of methane to produce hydrogen. The specific process is as follows:

[0044] First, take a certain amount of 20-50 mesh coconut shell activated carbon in a beaker, add deionized water and wash repeatedly to remove dust and impurities on the surface of the activated carbon until the washing water is clear, and then place the treated activated carbon in a drying oven at 105°C for 6 hours;

[0045] Secondly, take 100 ml of anhydrous sodium carbonate to prepare a 0.2 mol / L sodium carbonate solution, immerse 8 g of the cleaned coconut shell activated carbon completely in the sodium carbonate solution, and then place the solution in an ultrasonic cleaning machine for ultrasonic oscillation for 2 hours;

[0046] Then, the coconut shell activated carbon was taken out from the ultrasonic cleaning machine, and allowed to stand at room temperature. The activated carbon was stirred every 30 minutes to allow bubbles on its surface to escape. Finally, the modified coconut shell activated carbon was placed in a drying oven at 105°C and dried for 6 hours.

[0047] Finally, the coconut shell activated carbon was placed in a fixed bed reactor in a tubular furnace and N was introduced at 40 ml / min. 2 , the temperature in the tube furnace was raised to 1000 °C at 10 °C / min and maintained for 3 h to remove the volatile matter and bound water in the activated carbon.

[0048] The catalyst prepared by ultrasound-assisted modified carbon-based materials was used for methane catalytic cracking experiments. The experiment was carried out in a quartz tube reactor in a tubular furnace. The specific structure was adopted in Study on the mechanism of constructing structure defects on surface of activated carbon with carbon black to promote hydrogen production by thermal-decomposition of methane, Fuel, Volume 361, 1April 2024, 130758. Figure 1 device.

[0049] The steps of catalytic cracking are as follows:

[0050] First, weigh 2g of catalyst and place it in the middle of the quartz tube reactor. Fix the two ends with quartz wool to prevent the catalyst from being blown out after the gas is introduced. Then, introduce 40ml / min of nitrogen to place the catalyst in an inert gas atmosphere. After 20 minutes, start the heating program and raise the temperature to 850-950℃ at 15℃ / min.

[0051] Then, the nitrogen gas was switched to methane gas, the methane gas flow rate was 20 ml / min, and the temperature was kept constant for 120 min;

[0052] Finally, the methane gas enters the quartz tube reactor, flows through the catalyst, and undergoes a methane catalytic cracking reaction to generate solid carbon and hydrogen. The reacted gas passes through the filter device and then enters the flue gas analyzer. The experimental data is monitored in real time through the instrument's built-in software.

[0053] The effect of methane catalytic cracking to produce hydrogen by the catalyst prepared by ultrasound-assisted modification was compared with that of the same amount of coconut shell activated carbon catalyst, and the temperature of the tubular furnace was set at 850°C, 900°C and 950°C.

[0054] The methane conversion rate is calculated according to the following formula:

[0055]

[0056] Methane conversion rate is shown in the attached Figure 2 As shown in the figure, the methane conversion rate of the catalyst prepared by ultrasound-assisted modification shows a similar trend at different temperatures, that is, the methane conversion rate is higher at the initial stage of the reaction, and as the reaction proceeds, the methane conversion rate decreases significantly; and the higher the temperature, the higher the methane conversion rate. This is because the methane cracking reaction to produce hydrogen is an endothermic reaction, and increasing the temperature helps the methane cracking reaction to move forward.

[0057] Comparative Example 1

[0058] A comparative experiment was set up according to the method of Example 1, and only the same amount of 20-50 mesh coconut shell activated carbon was calcined in a nitrogen atmosphere for 3 hours in the same calcination manner.

[0059] Compared with the unmodified catalyst, the catalyst prepared by ultrasound-assisted modification has a significant improvement in the catalytic methane cracking reaction at different temperatures. After 120 minutes of reaction, the methane conversion rate of the ultrasound-assisted modified activated carbon prepared by the present invention is 10% higher than that of the unmodified AC.

[0060] It is further explained that the catalyst prepared by the present invention through ultrasound-assisted modification of activated carbon can significantly improve the performance of catalytic methane cracking to produce hydrogen.

[0061] Figure 3 The surface microstructures of activated carbon catalyst and ultrasound-assisted modified activated carbon catalyst materials. Figure 3 (a)-(b)), the surface of the catalyst is porous, and its porous structure provides active sites for the adsorption and dissociation of methane molecules. Therefore, it has a certain catalytic effect on the cracking of methane to produce hydrogen. Compared with the unmodified activated carbon catalyst, it is found that the surface microstructure of the ultrasound-assisted modified activated carbon catalyst ( Figure 3 (c)-(d)) in Na 2 CO 3The pore size becomes larger under the erosion of the solution, and the cross section of the catalyst surface becomes more irregular, which makes the ultrasonic-assisted Na 2 CO 3 The specific surface area of ​​the catalyst increases after solution modification, which is beneficial to further improve the methane conversion rate.

[0062] The internal pore structure and adsorption characteristics of the catalyst material were further explored by BET test. Figure 4 According to the classification of the International Union of Pure and Applied Chemistry, AC, Na 2 CO 3 The isotherm adsorption curves of modified AC are all type I isotherms with H4 hysteresis loop, indicating that it is an irregular mesoporous structure.

[0063] Table 1 lists the pore characteristics of the catalysts.

[0064]

[0065] in, Figure 4 (b) shows the pore size distribution curve of the catalyst. Compared with AC material, it is found that after Na 2 CO 3 The activated AC catalyst has a higher mesoporosity. 2 CO 3 The specific surface area of ​​modified AC increased from 977.9119 to 1035.8383 m 2 / g, and the total pore volume and pore diameter also increased slightly, which is related to the etching of AC by sodium carbonate, making the catalyst surface more loose.

[0066] Embodiment 2-4

[0067] The catalyst prepared by ultrasound-assisted modification of carbon-based materials in Example 1 was used for methane cracking to produce hydrogen. The methane catalytic cracking experimental process was the same as in Example 1, except that the methane gas flow rate was changed to 5 ml / min, 10 ml / min and 15 ml / min. The results are as follows: Figure 5 shown.

[0068] When the methane gas flow rate is changed, the methane conversion rate changes significantly. When the methane gas is 5 ml / min, the methane conversion rate is the highest, and the conversion rate can still be maintained at about 70% after 120 min; further increasing the methane gas flow rate to 10 ml / min and 15 ml / min, the methane conversion rate will decrease to varying degrees during the reaction, but the final methane conversion rate is still improved compared with Comparative Example 1.

[0069] Embodiment 5-6

[0070] The concentration of sodium carbonate solution was changed to 0.05 mol / L, 0.1 mol / L, 0.4 mol / L and 0.6 mol / L sodium carbonate solution respectively. The other preparation processes were the same as in Example 1 to prepare modified catalysts with different concentrations of sodium carbonate solution. The methane cracking hydrogen production experiment was carried out. The temperature of the tubular furnace was set to 950°C. The other conditions were carried out with reference to Example 1. The methane conversion rate was as follows: Figure 6 shown.

[0071] Compared with the unmodified activated carbon catalyst, the activated carbon modified by any concentration of sodium carbonate solution can improve the methane conversion rate, and the modification by sodium carbonate solution can delay the deactivation of the catalyst.

[0072] Figure 7 The microscopic morphology of carbon-based materials modified by ultrasound-assisted treatment with different concentrations of sodium carbonate is shown in Figure 2. Figure 3 It was found that as the concentration of sodium carbonate increased, the etching effect on the activated carbon material increased; by comparing the catalytic activity of modified materials with different concentrations, it was found that the methane conversion rate was highest when the sodium carbonate solution was 0.2 mol / L. This is because the high concentration of sodium carbonate modification causes the activated carbon pore structure to collapse, affecting the adsorption and dissociation of methane molecules, thereby inhibiting the further improvement of catalytic activity.

[0073] In summary, the preparation process of the catalyst obtained by ultrasonic-assisted modification of carbon-based materials of the present invention has significant effects and adaptability, can significantly improve the methane conversion rate, and delay the deactivation of the catalyst. In addition, the preparation process of the catalyst of the present invention is simple, has a short cycle and low cost, and has significant application prospects and economic benefits.

[0074] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a catalyst by ultrasonically assisted modification of carbon-based materials, characterized in that: The following steps are involved: Step 1, preprocessing Take 20-50 mesh coconut shell activated carbon, wash it repeatedly with deionized water to remove dust and impurities on the surface of the activated carbon until the washing water is clear, dry it and set it aside; Step 2, ultrasonic treatment Take anhydrous sodium carbonate to prepare a 0.05-0.6 mol / L sodium carbonate solution, completely immerse the coconut shell activated carbon cleaned in step 1 in the sodium carbonate solution, and then place it in an ultrasonic cleaning machine for ultrasonic oscillation for 2 hours to obtain coconut shell activated carbon; Step 3, static modification Take out the coconut shell activated carbon after ultrasonic oscillation treatment, let it stand at room temperature, stir the activated carbon thoroughly every 30 minutes to allow the bubbles on its surface to escape, and finally dry it for use; Step 4, Calcination The coconut shell activated carbon modified in step 3 is placed in a tubular furnace, calcined under nitrogen protection, and kept warm for 3 hours to remove volatile matter and bound water in the activated carbon, thereby obtaining a catalyst.

2. The method for preparing a catalyst by ultrasonically assisted modification of carbon-based materials according to claim 1, characterized in that: The drying temperature in step 1 and step 3 is 105° C., and the drying time is 6 h.

3. The method for preparing a catalyst by ultrasonically assisted modification of carbon-based materials according to claim 1, characterized in that: The nitrogen introduction rate in step 4 is 40 ml / min.

4. The method for preparing a catalyst by ultrasonically assisted modification of carbon-based materials according to claim 1, characterized in that: The calcination temperature in step 4 is 1000° C. and the heating rate is 10° C. / min.

5. The catalyst prepared by the method according to claim 1, characterized in that: The catalyst has an irregular honeycomb porous structure, the pores are evenly distributed and have a large depth, and the surface roughness is significantly improved.

6. Use of the catalyst prepared by the method according to claim 1 in catalytic methane cracking to produce hydrogen.

7. The use according to claim 6, characterized in that: The cracking temperature is 900° C. and the methane gas flow rate is 5 ml / min.

Citation Information

Patent Citations

  • A method for preparing hydrogen and cellulose carbon using carbon materials as catalysts

    CN106865498B

  • Method for stably catalyzing methane cracking hydrogen production by using carbon black enhanced activated carbon and application

    CN113307225A